Magnetic Nanoparticles and Carbon Quantum Dots: Interdisciplinary Nanoparticles for Sensing and/or Education - Freire, Rafael Melo (2016)
FREIRE, Rafael Melo. Magnetic nanoparticles and carbon quantum dots: interdisciplinary nanoparticles for sensing and/or education. 182 f. 2016. Tese (Doutorado em Química)-Universidade Federal do Ceará, Fortaleza, 2016.